2021
DOI: 10.1002/cpp.2657
|View full text |Cite
|
Sign up to set email alerts
|

Preoccupation as psychopathological process and symptom in adjustment disorder: A scoping review

Abstract: In the ICD-11 diagnostic guidelines, preoccupation has been introduced as the new core symptom of adjustment disorder. Despite this essential innovation, preoccupation has so far largely been defined as rumination and worry and does not feature a distinct character as an independent symptom. In order to investigate the nature of preoccupation, various cognitive approaches are evaluated and linked to preoccupation. Furthermore, the aim of this review is to define preoccupation more precisely and to distinguish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
8

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 97 publications
0
13
0
8
Order By: Relevance
“…In line with this model, it was recently argued that preoccupation may represent a generic risk factor for the development of psychopathology [ 28 ]. The current study lends further support for the transdiagnostic potential of preoccupation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this model, it was recently argued that preoccupation may represent a generic risk factor for the development of psychopathology [ 28 ]. The current study lends further support for the transdiagnostic potential of preoccupation.…”
Section: Discussionmentioning
confidence: 99%
“…Supportive measures should guide clients to reprocess and understand their experiences in a meaning-making process. Clients must not develop avoidance strategies because attempts to suppress distressing thoughts about the event are often doomed to failure and can perpetuate the disorder in the long term [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), some of the core characteristics of adjustment disorder include preoccupation with the stressor in the form of excessive rumination, worry, and recurrent distressing thoughts. Psychological interventions targeting these thought processes may lead to significant positive outcomes [ 10 ]. In a single case study, MCT was found to be helpful in managing symptoms of depression and anxiety in a young woman diagnosed with severe adjustment disorder secondary to pulmonary arterial hypertension [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…Auch wenn z.B. eine Scheidung eine enorme Herausforderung für Betroffene bedeuten kann, so sind solche Ereignisse zum Zeitpunkt der Exposition typischerweise nicht identitätsbedrohend und ziehen deshalb auch nicht die typischen PTBS-Symptome nach sich [Brewin, 2009;Eberle and Maercker, 2022].…”
Section: Anpassungsstörungunclassified